(untitled) (Principles of Medical Toxicology, 2025)
Author Mr. Mushraff Ali Khan M, Associate Professor, Department of Pharmaceutics, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, India Abstract The knowledge about how the toxic substances enter, distribute through, transform within, and exit the body is fundamental to predicting, preventing, and treating poisonings. Toxicokinetics is the study about absorption of xenobiotics through gastrointestinal, dermal, pulmonary, and parenteral routes, each with distinct characteristics affecting the rate and extent of entry into circulation. Once absorbed, distribution is influenced by factors including protein binding, lipid solubility, and specialized barriers such as the blood-brain and placental interfaces. Metabolism, primarily occurring in the liver, encompasses Phase I (functionalization) and Phase II (conjugation) reactions that can either detoxify harmful substances or bioactivate relatively innocuous compounds into toxic metabolites. Excretion pathways—renal, biliary, pulmonary, and others—complete the ADME process, with parameters like half-life and clearance rate determining how long toxins persist. Toxicodynamics addresses mechanisms by which substances produce adverse effects, including receptor interactions, enzyme inhibition, protein and DNA adduct formation, oxidative stress, and disruption of cellular homeostasis. These principles provide the mechanistic foundation for clinical toxicology, explaining why certain exposures produce specific symptoms and guiding the development of targeted therapeutic interventions Keywords: Toxicokinetics, Toxicodynamics, Biotransformation, Bioactivation, Xenobiotic Metabolism, Cellular Toxicity VIEW PDF